Evaluasi Kebijakan Pelayanan Administrasi Terpadu Kecamatan (PATEN) Pada Kecamatan Sawangan Kota Depok - Jeihan Mahendra Putra; Abdul Rahman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Local governments play a strategic role in public service delivery and are required to undertake rapid, systematic, and sustainable institutional and governance transformation. These demands arise in response to changes in the organizational environment, regulatory developments, and increasing public expectations regarding the quality, effectiveness, and accountability of public services. Improving the capacity of human resources, particularly those managing services and complaints, is a crucial factor in ensuring professional, adaptive, and technology-based services. However, issues with staff competency are still found in public service institutions that interact directly with the public, particularly at the sub-district level. In an effort to improve the quality of public administration services, the government established the Integrated Sub-district Administrative Services (PATEN) policy as stipulated in Minister of Home Affairs Regulation Number 4 of 2010. This study aims to analyze the implementation of the PATEN policy in Sawangan District, Depok City, using a qualitative approach and descriptive methods. The results indicate that the implementation of PATEN has generally been effective, marked by the fulfillment of substantive, administrative, and technical aspects, and supported by clear regulations. However, public complaint services have not been optimal due to technical constraints in the website-based complaint system.